Prevention of cytomegalovirus disease in patients with impaired cell-mediated immunity – is there a need for maribavir?. (October 2013) - Bommer, Martin; Michel, Detlef
Abstract : Introduction: Human cytomegalovirus (HCMV) infections are still significant causes of morbidity and mortality in transplant recipients. Approved compounds ganciclovir (GCV), foscarnet (FOS) and cidofovir (CDV) are limited by toxicity and evolving resistance in patients with impaired cell-mediated immunity. New substances with new mechanisms of action and lesser toxicity issues are required.Maribavir (MBV) is a benzimidazole l-riboside and acts as a competitive inhibitor of the HCMV UL97 protein. MBV was discovered at the University of Michigan and originally developed by GlaxoSmithKline. In 2003, the substance was licensed to ViroPharma. The drug is orally applicable and exhibited antiviral potency against different HCMV strains including strains resistant to GCV, CDV and FOS. Areas covered: This article examines the published pharmacokinetic, safety and efficacy data from Phase I, Phase II and Phase III studies as well reports of antiviral resistance. Expert opinion: Although MBV exhibits a desired new mechanism of action, the compound showed limitations in recent Phase III clinical trials. Proposed explanations include an inadequate dosing regimen and choice of study endpoint. Therefore, MBV deserves further systematic evaluation and its optimal dose has to be determined. Hence, the results of the new Phase II study with different doses of MBV for treatment of HCMV will be a crucial milestone.